(untitled) (International Journal of Engineering and Computer Science, 2013)
All different types of internet services which are very popular these days in the life of human, now a day’s every person’s life become nothing without internet services. For fulfilling the user requirements this work on both the ends like front end & back end. On front end user can access to the respective internet services & o back end according to the user requirement the data which is vto the user is provided. This strategy is mainly focus on to detect intrusion in multi-tier web applications. Multi-tier web application include two ends that is front end as well as back end of the applications. The front end include web server which can responsible to run the application and gives that output to back end i.e. file server. This strategy is useful to identify the intrusion at both front end and back end of web application. It is used to monitor the behavior across front end web server and back end database server or file server using IDS. We will also able to detect intrusion in static and dynamic web application. IDS having maximum accuracy and is mainly responsible to identify intrusion.